2020
DOI: 10.1371/journal.pone.0233428
|View full text |Cite
|
Sign up to set email alerts
|

Response of glyphosate-resistant and susceptible biotypes of Echinochloa colona to low doses of glyphosate in different soil moisture conditions

Abstract: To evaluate the hormetic effect of glyphosate on Echinochloa colona, two pot studies were done in the screenhouse at the Gatton Campus, the University of Queensland, Australia. Glyphosate was sprayed at the 3-4 leaf stage using different doses [(0, 5, 10, 20, 40, 80 and 800 g a.e. ha-1) and (0, 2.5, 5, 10, 20 and 800 g a.e. ha-1)] in the first and second study, respectively. In the second study, two soil moistures (adequately-watered and waterstressed), and two E. colona biotypes, glyphosate-resistant and glyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The absorption of low doses of glyphosate may vary according to the water conditions of the plant. Plants may require higher doses of glyphosate when under water deficit, this effect being due to the translocation capacity of the herbicide in the plant 28,32 . The hormeticdose for stimulation in plants under water deficit was on average lower than under no water stress (60.27 ± 11.30 g a.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The absorption of low doses of glyphosate may vary according to the water conditions of the plant. Plants may require higher doses of glyphosate when under water deficit, this effect being due to the translocation capacity of the herbicide in the plant 28,32 . The hormeticdose for stimulation in plants under water deficit was on average lower than under no water stress (60.27 ± 11.30 g a.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the interaction between water deficit and glyphosate hormesis in plants are rare; however, previous studies with Phaseolus vulgaris have shown a greater tolerance to water stress in the presence of low doses of glyphosate 31 . Research has shown that the effectiveness of glyphosate is dependent on climatic conditions, the susceptibility of the crop to glyphosate and the stage of plant development, however this work was conducted mostly with weeds 28,32 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations